2021
DOI: 10.3389/fimmu.2021.641655
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Antibody-Associated Vasculitis With Acute Kidney Injury: Short-Term Recovery Predicts Long-Term Outcome

Abstract: BackgroundKidney involvement is common in antineutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV). It tends to be aggressive, and in some patients, the kidney involvement may reach the criteria of acute kidney injury (AKI). Here, we aim to describe the clinical characteristics of these patients and find risk factors for poor outcomes.MethodsPatients diagnosed with AAV in our hospital from February 2003 to February 2017 were included. Those who reached the KDIGO AKI criteria were reclassified acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These differences could be related to the fact that weight loss, which is also a sign of frailty, is a component included in the general manifestation of Birmingham Vasculitis Activity Score and renal involvement is one of the most life-threatening complications of AAV. 41,42 Our study identified that there is a relationship between sarco- inexpensive tests and have been shown to predict poor outcomes in various populations. 43 Hence, it would be of importance to develop practical measures for assessing sarcopenia besides NAMA/ TAMA ratio, that could aid in identifying AAV patients at greater risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These differences could be related to the fact that weight loss, which is also a sign of frailty, is a component included in the general manifestation of Birmingham Vasculitis Activity Score and renal involvement is one of the most life-threatening complications of AAV. 41,42 Our study identified that there is a relationship between sarco- inexpensive tests and have been shown to predict poor outcomes in various populations. 43 Hence, it would be of importance to develop practical measures for assessing sarcopenia besides NAMA/ TAMA ratio, that could aid in identifying AAV patients at greater risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…Our results found that NAMA/TAMA differed in those showing the clinical features of general and renal manifestation compared with those without these features. These differences could be related to the fact that weight loss, which is also a sign of frailty, is a component included in the general manifestation of Birmingham Vasculitis Activity Score and renal involvement is one of the most life‐threatening complications of AAV 41,42 …”
Section: Discussionmentioning
confidence: 99%
“…Kidney involvement is common and main manifestation of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis presented as glomerulonephritis in the disease course [7] . We reported a case of a 28-year-old male patient with comorbid SSc and AAV.…”
Section: Highlightsmentioning
confidence: 99%